A rare case of coexistence of bicornuate and septate uterine malformation - Chouhan, Tulika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Congenital uterine anomalies result from defects in the formation, fusion, or resorption of the Müllerian ducts during embryogenesis. Patients commonly present with infertility, recurrent pregnancy loss, preterm labor, or abnormal fetal presentation, though some anomalies are detected incidentally on imaging. The most frequent congenital anomaly is septate uterus. We report an unusual case of coexistence of septate uterus with bicornuate morphology in a woman presenting with primary infertility.